Trends in outcomes, complications, and hospitalization costs for hemispherectomy in the United States for the years 2000–2009. (20th December 2014) - Lin, Yimo; Harris, Dominic A.; Curry, Daniel J.; Lam, Sandi
Summary Objective Hemispherectomy is an established surgical treatment for carefully selected pediatric patients with intractable epilepsy. Published perioperative data report low mortality rates and seizure reduction rates of 50–89%. This study investigates trends in the demographics, hospital utilization, and in‐hospital complication rates of patients undergoing hemispherectomy over the past decade in the United States, using the nationally representative Kids' Inpatient Database (KID). Methods The KID was queried for all discharges with the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) procedure code for hemispherectomy in the years 2000, 2003, 2006, and 2009. The patient cohorts from these four time points were compared, analyzing differences in demographic data, insurance and payer status, total cost, length of stay, in‐hospital mortality, and complications. National estimates and 95% confidence intervals are reported given the weighted sample design of KID. Results This study identified an estimated total of 552 hospital admissions for hemispherectomy surgery during the years studied in this cohort. The incidence of this procedure increased from 1.2/100, 000 admissions in 2000 to 2.2/100, 000 in 2009 (p = 0.05). Mean age was 6.7 years (range 0–20). There were no significant changes in demographics (age, gender, or race), hospital descriptors (size or type), insurance type, or zip code income quartile. There was a significant increase in total cost, from 42, 807 in 2003 to 57, 443 in 2009 (p = 0.015) (adjusted to 2009 dollars). There were no trends in postoperative complications. In‐hospital mortality occurred in five subjects (0.9%). Ventricular shunt placement during hemispherectomy hospitalizations increased over time from 6.7% to 16.5% (p = 0.056). Hospitals that performed two or more hemispherectomies yearly had a significantly decreased incidence of in‐hospital mortality (odds ratio [OR] 0.08, p = 0.04) and an increased incidence of blood transfusion (OR 3.7, p = 0.01) compared to hospitals that performed 0–1 procedures a year. Significance Hemispherectomy procedures increased slightly in frequency over the past decade, with no change in demographic characteristics of the patients over time. Rates of mortality and perioperative complications remained low. Total costs have increased significantly over time. In‐hospital mortality was lower in higher volume hospitals.